Steel magnolias [videorecording (Blu-Ray)] - Harling, Robert, 1951-; Field, Sally; MacLaine, Shirley, 1934-; Dukakis, Olympia; Parton, Dolly; Hannah, Daryl; Roberts, Julia, 1967-; Skerritt, Tom; McDermott, Dylan; Shepard, Sam, 1943-2017 (Sony Pictures Home Entertainment, 2019)
A heartwarming story of life, love, and loss in a small Louisiana parish. At the center of the group is Shelby Eatenton, newly married and joyfully pregnant, despite the fact that her diabetes could make childbirth life threatening. Terrified and angry at the possibility of losing her only daughter, M'Lynn Eatenton looks to her four closest friends for strength and laughter as she battles her deepest fear of death in order to join Shelby in celebrating the miracle of new life.